GENDER DISCRIMINATION IN MIMI LEDER'S ON THE BASIS OF SEX MOVIE (Universitas Pamulang, 2019)
This study is aimed to discuss the forms of gender discrimination against women in the film â€œOn the Basis of Sexâ€ directed by Mimi Lederâ€™s. This research focuses on the analysis of visual images that represent social life or social action in the film. In the film analyzes a woman who wants to get the same rights to men by putting forward Beauvoir's theory. The emergence of this form of discrimination still has a relationship and influence with each other and also has a perspective or model of understanding in looking at gender. One of them in this film is that men who dominate women. The theory used is Simone De Beauvoir state that in some societies had successful revolutions in other parts of the world but still the status of the subordination of women remains and the male domination has been an acceptable and invisible reality.Keywords: Gender Discrimination, Male Domination, Second Sex, Simone De Beauvoir.